Regulated Carbon Market and Carbon Credits in Brazil: accounting and taxation issues - Souza, André Luis Rocha de; Alvarez, Guineverre; Andrade, José Célio Silveira (Organizações & Sociedade, 2014)
This paper seeks to discuss accountancy and tax discrepancies related to Certified Emission Reductions (CERs) in Brazil’s regulated carbon market, highlighting the gaps and weaknesses, presenting points to be considered in the creation of a regulatory framework and an accounting classification for CERs, and recommending an institutional arrangement to this effect. Bibliographic and documentary research was conducted in order to achieve these objectives, which led to the development of a conceptual framework for analysis. Evidence suggests that the regulated carbon market in Brazil lacks norms, creating diversity in the classification of and accounting for carbon credits. There is a tendency to recognize them as stock, since any financial benefits accrued by their sale may be accounted as a factor in reducing a company’s production costs. From a tax perspective, questions remain about the revenue framework for carbon credits traded with foreign countries, given their lack of a legal definition. Finally, we establish a institutional arrangement to set out guidelines for the regulation of the sector in Brazil.